Pengaruh Penggunaan Buku Bahasa Arab Berbasis Kompetensi Terhadap Kemahiran Bahasa Arab Siswa Kelas VII MTS Al Raisiyah Sekarbela - Ilyas Mulyasa Salsabil; Khairul Amar; Miftahul Jannah; Yulianti Yulianti; Nasarudin Nasarudin (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2026)
This study aims to determine the effect ofusing Arabic textbooks on the Arabic language proficiency of seventh grade studentsat MTs Ar Raisiyah Sekarbela. Textbooks play an important role in supporting thelearning process because they contain material, exercises, and instructionsthat serve as guidelines for teachers and students. However, the effectiveness of Arabic textbooks in improving students' language proficiency has rarely been measured empirically. Therefore, this study was conducted to examine the extent to which the use of Arabic textbooks affects students' abilities in the four main Arabic language skills, namely listening (الاستماع), speaking (الكلام), reading (القراءة), and writing (الكتابة). This study used a quantitative approach with a quasi-experimental design, with a one-group pre-test and post-test design. The research sample consisted of 22 seventh-grade students at MTs Ar Raisiyah Sekarbela who were selected using purposive sampling. Data were collected through test instruments compiled based on two variables, namely the use of Arabic textbooks (variable X) and Arabic language proficiency (variable Y), along with their respective indicators. Data analysis was performed using a t-test (paired sample t-test) to determine the difference between the pre-test and post-test results. The results of the study are expected to show a significant increase in Arabic language proficiency scores after students systematically and purposefully used Arabic language books. Thus, it can be concluded that the use of Arabic language books that are tailored to students' needs, didactically complete, and visually appealing has a positive effect on improving Arabic language proficiency.